Isorhamnetin: what is the in vitro evidence for its antitumor potential and beyond? - Lei, Jiaming; Yang, Jianbao; Bao, Cuiyu; Lu, Feifei; Wu, Qing; Wu, Zihan; Lv, Hong; Zhou, Yanhong; Liu, Yifei; Zhu, Ni; Yu, You; Zhang, Zhipeng; et al. (Frontiers in Pharmacology, 2024)
Isorhamnetin (ISO) is a phenolic compound belonging to flavonoid family, showcasing important in vitro pharmacological activities such as antitumor, anti-inflammation, and organ protection. ISO is predominantly extracted from Hippophae rhamnoides L. This plant is well-known in China and abroad because of its “medicinal and food homologous” characteristics. As a noteworthy natural drug candidate, ISO has received considerable attention in recent years owing to its low cost, wide availability, high efficacy, low toxicity, and minimal side effects. To comprehensively elucidate the multiple biological functions of ISO, particularly its antitumor activities and other pharmacological potentials, a literature search was conducted using electronic databases including Web of Science, PubMed, Google Scholar, and Scopus. This review primarily focuses on ISO’s ethnopharmacology. By synthesizing the advancements made in existing research, it is found that the general effects of ISO involve a series of in vitro potentials, such as antitumor, protection of cardiovascular and cerebrovascular, anti-inflammation, antioxidant, and more. This review illustrates ISO’s antitumor and other pharmacological potentials, providing a theoretical basis for further research and new drug development of ISO.